2019
DOI: 10.1002/cncr.31942
|View full text |Cite
|
Sign up to set email alerts
|

Biliary tract cancer incidence and trends in the United States by demographic group, 1999‐2013

Abstract: Background Biliary tract cancers (BTCs) are rare but deadly cancers (gallbladder cancer [GBC], intrahepatic cholangiocarcinoma [ICC], extrahepatic cholangiocarcinoma [ECC], and ampulla of Vater cancer [AVC]). A recent US study reported increasing GBC incidence among people younger than 45 years and blacks; however, it did not examine trends for other biliary tract sites. Methods This study characterized demographic differences in BTC incidence rates and time trends by anatomic site. Population‐based North Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
110
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 127 publications
(132 citation statements)
references
References 40 publications
9
110
0
2
Order By: Relevance
“…1 Between 2003 and 2009, an annual 5.9% increase in the incidence of iCCA was reported in the United States. 2 This sustained increase throughout all ages and ethnicity strata 3 has also been seen in European countries, [4][5][6] paralleled by an increase in iCCA-specific mortality. 7 Negative trends in iCCA incidence and mortality could be partially explained by improved diagnosis tools, more specific classification and increases in risk factors such as chronic hepatitis, metabolic syndrome and obesity.…”
Section: Introductionmentioning
confidence: 69%
“…1 Between 2003 and 2009, an annual 5.9% increase in the incidence of iCCA was reported in the United States. 2 This sustained increase throughout all ages and ethnicity strata 3 has also been seen in European countries, [4][5][6] paralleled by an increase in iCCA-specific mortality. 7 Negative trends in iCCA incidence and mortality could be partially explained by improved diagnosis tools, more specific classification and increases in risk factors such as chronic hepatitis, metabolic syndrome and obesity.…”
Section: Introductionmentioning
confidence: 69%
“…Six (four high and two moderate quality) of the eight included studies reported increasing trends, and two (both moderate quality) found decreasing trends (Figure 2, Table 1, Supplementary Table 3.4). All three studies from the USA (64)(65)(66) and one from the Netherlands (70) described increasing short-or long-term trends among persons over recent decades until at least the late 2000s. While sex-specific rates increased from 1999 to 2005 (68) in South Korea, another study from the same country reported decreasing trends among persons over the decade until 2015 (67).…”
Section: Intrahepatic Cholangiocarcinomamentioning
confidence: 99%
“…While long-term trends increased across all ages in the USA until 2013 (66), they were stable among all age groups except those aged 45-59 years, for whom they increased from 1989 to 2009 in the Netherlands (70) ( Table 2).…”
Section: Trends By Agementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the incidence of CCA tends to show a worldwide rise, especially ICC [3][4][5][6]. In US, ICC age-adjusted incidence rate increased from 1.42 to 1.82/100,000 in males and from 0.98 to 1.45 in females between 1999 and 2013 [8]. Notably, the increasing ICC incidence is thought to be influenced by the criteria modification of CCA classification in the International Classification of Diseases for Oncology (ICD-O) coding system [3,9].…”
Section: Introductionmentioning
confidence: 99%